Fikih Wanita tentang Menstrual Hygiene dan Mitos yang Berkembang di Masyarakat dalam Perspektif Islam - Indana Wardahtul Maulidah (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss Islamic fiqh law and myths in society about menstrual hygiene. The author uses a qualitative descriptive method that focuses on a number of data obtained from written academic sources to answer questions related to the theme raised. The concept of Islamic jurisprudence by al-Ghazali in this study occupies a formal object. While the idea of menstrual hygiene becomes its material object. The myths that develop in society become its scope. The myth is a prohibition against cutting nails, cutting hair, washing hair, even combing. This research reveals that this myth should not develop in society because it will only cause many health problems, especially in Islam maintaining cleanliness is an important thing that reflects a servant of God Allah SWT who likes cleanliness.